Current Challenges in Fecal Microbiota Transplantation for Clostridioides difficile Infection in Children. (18th September 2021) - Nicholson, Maribeth R.; Hourigan, Suchitra K.; Conrad, Maire; Goyal, Alka; Jensen, Kyle; Kelsen, Judith; Kennedy, Melissa; Weatherly, Madison; Kahn, Stacy A.
Abstract : INTRODUCTION: The impact of the 2019 US Food and Drug Administration safety alert involving transmission of multidrug resistant organisms through fecal microbiota transplantation (FMT), and the COVID-19 pandemic on the use of FMT in children, is unknown. METHODS: A survey of pediatric gastroenterologists performing FMT for Clostridioides difficile infection was conducted. RESULTS: Of 36 respondents, 17 (47%) and 30 (83%) changed their FMT practices related to the US Food and Drug Administration safety alert and COVID-19 pandemic, respectively, with 22 (61%) of programs halted. DISCUSSION: The US Food and Drug Administration safety alert and COVID-19 pandemic have substantially influenced the availability and access of FMT for children.